Sex differences in the severity of presbyopia with dry eye: A cross-sectional retrospective study - Masahiko Ayaki; Akiko Hanyuda; Kazuno Negishi (PLoS ONE, 2025)
Purpose Visual symptoms in older people may derive from presbyopia and dry eye (DE) with sex-specific pathology. Previous studies have suggested women may have a greater risk for presbyopia than men of the same age. However, the association between DE, which is more frequent in women, and presbyopia has not been determined. This study explored whether the relationship between DE and the severity of presbyopia differs by sex. Methods This cross-sectional retrospective cohort study included 1147 bilateral phakic patients, aged from 40 to 55 years (858 women and 289 men). Refraction, near add power at 30 cm, and DE-related clinical parameters (corneal staining score and tear break-up time [BUT]) were compared between the sexes. Correlation analyses and odds ratio comparisons of risk factors for reaching specific near add power (1.00, 1.25, 1.50, and 1.75 D) were performed. Results Corneal staining and tear break-up time (BUT) were worse in women. Correlation analysis stratified by sex revealed that near add power correlated with age (women: β = 0.80, P < 0.01; men: β = 0.80, P < 0.01), and astigmatic errors (women: β = 0.16, P < 0.01; men: β = 0.19, P < 0.01) in both sexes, BUT only in women (β = −0.10, P < 0.01), and corneal staining only in men (β = 0.20, P < 0.01). Women with short BUT and men with corneal staining were more likely to reach higher near add power. Conclusion The current study suggests that men with corneal staining and women with short BUT may need more near add power. These DE-related clinical features are significant factors for presbyopia and should be managed to ameliorate presbyopia-related symptoms.